Pengaruh Biaya Produksi Dan Biaya Operasional Terhadap Laba Bersih Melalui Volume Penjualan Di UD. Gajah Tempur - Eka Dian Puspita; Ilvi Nur Widiana; Rofiatul Adwiyah Mufidah; M. Maulana Nasir; M.Aldi Al Fauji (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to examine the relationship between production costs and net profit, sales volume, operational costs and net profit, sales volume, as well as the relationship between net profit and sales volume. This research utilizes a quantitative approach using the Partial Least Square (PLS) method. The population in this research is the sales data at UD. Gajah Tempur, and the sample in this research adopts a non-probability sampling design with a saturated sample of 39 respondents. The analysis techniques employed in this research are descriptive analysis and inferential statistical analysis using the Partial Least Square (PLS) method. The results of the research indicate that production costs have a positive but insignificant influence on net profit. Production costs also have a positive influence on sales volume. Meanwhile, operational costs have a positive but insignificant influence on net profit, but they have a positive influence on sales volume. Furthermore, net profit has a positive but insignificant influence on sales volume.